Serum protein C, Willebrand factor, platelet aggregation and structural and functional changes of the heart in patients with Q-wave myocardial infarctoin with acute left ventricle aneurism - V.D. Syvolap; S.M. Kiselev (Zaporozhye State Medical University, 2012)
Abstract In 120 patients with acute Q-wave myocardial infarction levels and correlations of Protein C, Willebrand Factor, platelets aggregation and structural-functional heart indexes were investigated depending on left ventricle aneurism formation. In patients with Q-wave myocardial infarction and acute left ventricle aneurism significant enlargement of left atrium accompanied by early formation of diastolic dysfunction of II type was noted; in blood serum lower level of Protein C and increased content of Willebrand Factor were revealed. Correlation analysis revealed interrelations between indexes of platelets aggregation, coagulation hemostasis and heart remodeling in patients with Q-wave myocardial infarction and left ventricle aneurism.